Evaluation the Ability of Standard Germination Test to Predict Emergence and Establishment of Chickpea (Cicer arietinum L.) Seedlings in Field - P. Bayat; M. Ghobadi; M.E. Ghobadi; Gh.R. Mohammadi (علوم و فناوری بذر ایران, 2016)
ABSTRACT In order to study the ability of standard germination test to predict emergence and establishment of chickpea seedlings in field, an experiment was conducted under two conditions using thirteen seed lots of chickpea in laboratory and research field at the College of Agriculture and Natural Resources, Razi University, Kermanshah, Iran, in 2012. In laboratory, thirteen seed lots of chickpea belonged to seven cultivars were planted as a randomized complete design with four replications using International Seed Testing Association methods. In this test, different indices related to seed and seedling vigor were evaluated. These seed lots were also planted under field condition in a randomized complete block design with four replications and percentage and rate of seedling emergence were evaluated. The results of analysis of variance in the laboratory test showed that seed lots differed significantly in final germination percentage, strong seedling percentage, abnormal seedling percentage, not-germinated seeds percentage, mean time germination, germination rate, germination index, seedling vigor index. Comparison of laboratory and field experiments showed that the new seed lots had higher germination characteristics than the old seed lots. Correlation between measured traits in standard germination test under laboratory condition with field condition showed that the percentage and rate of seedling emergence had higher correlation with final germination percentage, seedling strong percentage and seedling vigor index. Thus, the standard germination test had high ability for predict percentage and rate of seedling emergence in field